A comparative study on the influence of translanguaging in grade 4 life skills classroom at Greenvalley Circuit, Bohlabela District, Mpumalanga Province - Malebe, Phetolo Nicoline (My University, 2021)
Majority of South African learners come from diverse linguistic, social and cultural backgrounds. Therefore, their diversities in classroom require learning and teaching approaches that are capable of ensuring that classroom interactions fulfil learners’ multilingual needs and also help to improve the learning conditions–and thus the educational system of the country. Learners in South African rural and township schools have limited exposure to English. They come from impoverished backgrounds in which English does not form part of their daily communication, except that they are only exposed to the language at school. Translanguaging seems to be an approach that can be implemented to overcome language barriers in classrooms and resolve the challenges pertaining to the educational system of South Africa. This study aims to disclose how Translanguaging can be implemented to disrupt power imbalances of languages and how its implementation can create an inclusive classroom. The aim of this study is to investigate the benefits of using Translanguaging in a Grade 4 during Life Skills lessons. The study used a qualitative research methodology and adopted a comparative research design. The study has found that learners learn better in a language that they are proficient in. The implication to this finding is that policy makers must be advised to either add Translanguaging as a learning model to the existing models or redesign the existing models to bring transformation as well as to promote African languages as media of instruction
Thesis(M. A. (Language Education)) -- University of Limpopo, 2021
Keywords: Translanguaging; Linguistics; Multilingual education; Teaching; Translanguaging (Linguistics); Multilingual education; Language and languages -- Study and teaching; English language -- Study and teaching -- Bilingual method